Blood loss during surgery - Safer, Peter (1953)
Accurate knowledge of the total blood loss during surgery, helps to get maximum benefit from transfusions. Blood should be given to the volume and rate of loss. The maintenance of circulating volume of red blood cells in the normal range, should consider it as an elementary fact in surgery patients with poor surgical risk, particularly in heart, arteriosclerotic and those elderly who can not tolerate either an overload or a decrease in circulating volume. The methods used to measure blood loss during surgery are discussed. The authors apply the gravimetric method and recommend it as a routine procedure during surgery. A personal estimates of total blood lost during surgery is worthless. When it comes to control massive bleeding from several liters, the error can be so large that a lack of action may endanger the patient's life. The total blood loss during the operation obtained by the method recommended by the authors, is the minimum that should be replaced. Additional Sources of blood loss can not be determined by the gravimetric method are discussed. Numbers of blood loss in surgical operations obtained by Bonica and Lyter (561 cases), other (reported by Bonica and Lyter), and authors (109 cases) are presented. It is noted that blood loss during surgery is usually greater than the surgeon suspects. Blood loss of various operations is discussed and even large individual variation in the operations of the same type is annotated.